On the Minimum Feedback Vertex Set Problem: Exact and Enumeration Algorithms - Fomin, Fedor V.; Gaspers, Serge; Pyatkin, Artem V.; Razgon, Igor (Algorithmica, 2008)
We present a time algorithm finding a minimum feedback vertex set in an undirected graph on n vertices. We also prove that a graph on n vertices can contain at most 1.8638 n minimal feedback vertex sets and that there exist graphs having 105 n /10 ≈1.5926 n minimal feedback vertex sets.